Design of nutraceutical–mesoporous silica nanoconjugates - Marinheiro, Diogo Filipe Pires (2021)
Resveratrol (RSV) is a nutraceutical naturally present in various foods such as red wine, grape skins, peanuts, among many others. This compound has beneficial properties for human health such as antioxidant, anti-inflammatory and anticancer activities, among others. However, due to is physicochemical characteristics, mainly its low solubility in water that results in low bioavailability, the applicability of this compound is limited. In order to overcome these limitations, nanocarriers based approaches have emerged in the last years. The present work shows the results of the synthesis and characterization of mesoporous silica nanoparticles (MSNs) and evaluates their capacity to encapsulate and in vitro release RSV. With this purpose several synthesis conditions were investigated and two RSV loading methods were tested, by immersion and evaporation. The latter proved to be more effective allowing higher loads. The in vitro release studies suggest an increase in water solubility of the encapsulated RSV, when compared to the free one, and a faster release in acidic medium.